2016
DOI: 10.1016/j.cub.2016.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Crossmodal Association of Visual and Haptic Material Properties of Objects in the Monkey Ventral Visual Cortex

Abstract: Just by looking at an object, we can recognize its non-visual properties, such as hardness. The visual recognition of non-visual object properties is generally accurate [1], and influences actions toward the object [2]. Recent studies suggest that, in the primate brain, this may involve the ventral visual cortex, which represents objects in a way that reflects not only visual but also non-visual object properties, such as haptic roughness, hardness, and weight [3-7]. This new insight raises a fundamental quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 44 publications
2
27
0
Order By: Relevance
“…Both regions exhibit strong connections with AIP, which has been shown to represent the shape, size, and orientation of 3D objects, as well as the shape of the handgrip, grip size, and hand-orientation(46). Additionally, visual material properties, including object weight, are thought to be encoded in the ventral visual cortex(4751), and it has been suggested that AIP might play a unique role in linking components of the ventral visual stream involved in object recognition to hand motor system(52). Therefore, the neural circuit formed between F5, F2, and particularly AIP is a strong candidate for combining the multifaceted components of visually guided grasping identified in this work(5357).…”
Section: Discussionmentioning
confidence: 99%
“…Both regions exhibit strong connections with AIP, which has been shown to represent the shape, size, and orientation of 3D objects, as well as the shape of the handgrip, grip size, and hand-orientation(46). Additionally, visual material properties, including object weight, are thought to be encoded in the ventral visual cortex(4751), and it has been suggested that AIP might play a unique role in linking components of the ventral visual stream involved in object recognition to hand motor system(52). Therefore, the neural circuit formed between F5, F2, and particularly AIP is a strong candidate for combining the multifaceted components of visually guided grasping identified in this work(5357).…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, there have to be more elaborate computations that can later judge materials in a more fine-grained manner, carried out in higher visual areas. Such computations could, for example, take 3-dimensional information into account to determine a surface’s roughness, or access haptic representations of a surface ( Goda et al, 2016 ). So, even though low-level statistics, namely pixel statistics, filter parameters and spatial frequency information seem to play a role in material perception, mid- and high-level areas of the visual system must be involved in the perception of material properties.…”
Section: Discussionmentioning
confidence: 99%
“… Baumgartner et al (2013) found visual and haptic representations to be tightly linked. This is likely to be the result of learning processes ( Goda et al, 2016 ). Therefore it is difficult to attribute certain properties to one of the senses but from our earlier work it seems that texturedness can be judged more reliably in the visual sense, while roughness is a property that is easily and reliably accessible to both senses from an object’s material surface.…”
Section: Methodsmentioning
confidence: 99%
“…The neural basis of material category perception has been investigated in humans 14 , 15 and monkeys 2 , 3 . Functional magnetic resonance imaging (fMRI) studies revealed cortical activation in the ventral visual pathway in relation to visual-based material perception; the fusiform gyrus in humans 15 and the inferior temporal cortex in monkeys 2 , 3 . On the other hand, the activation in the ventro-medial pathway was demonstrated in relation to auditory-based material perception in humans 14 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the activation in the ventro-medial pathway was demonstrated in relation to auditory-based material perception in humans 14 . However, these studies focused on the high-order visual areas, where material information could be processed progressively 2 . Goda et al .…”
Section: Introductionmentioning
confidence: 99%